1993
DOI: 10.1055/s-2008-1053827
|View full text |Cite
|
Sign up to set email alerts
|

Klinik und Pathologie intrakranieller Subependymome - 18 eigene Fälle und Literaturübersicht

Abstract: Intracranial subependymomas are rare, benign tumours (WHO grade I) occupying a special position compared to the other ependymal neoplasms. They often remain asymptomatic and, in consequence, are found incidentally at autopsy. In the present study clinico-pathological data of 84 symptomatic (8 own cases) and 58 asymptomatic tumours (10 own cases) are summarised. Subependymomas are more frequently situated in the fourth (58.4%) than in the lateral ventricle (38.0%). They occur predominantly in middle-aged and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The largest case series published to date describe an incidence of 0.4-0.7%, which is larger in middle-aged or senior males, with a mean age of presentation between 48.5 and 53.6 years. [3121619] Epidemiologically, our patient coincides with the international observations reported in the literature.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The largest case series published to date describe an incidence of 0.4-0.7%, which is larger in middle-aged or senior males, with a mean age of presentation between 48.5 and 53.6 years. [3121619] Epidemiologically, our patient coincides with the international observations reported in the literature.…”
Section: Discussionsupporting
confidence: 89%
“…[3] Tumors located on the septum pellucidum and the foramen of Monro are more prone to cause CSF obstruction, and typical symptoms include headaches, nausea, vomiting, seizures, ataxia, and vertigo. [341218] The size of the lesion also plays a very important role in the clinical expression of subependymomas; Akamatsu et al . found that the majority of symptomatic tumors had a diameter of approximately 4 cm, whereas asymptomatic ones measured 0.8 cm on average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation